DOSE-FINDING STUDY AND PHARMACODYNAMIC ASSESSMENT OF PROPOFOL FOR (SEMI-)ELECTIVE INTUBATION IN NEONATES. Issue 1 (14th December 2015) - Smits, Anne; Thewissen, Liesbeth; Caicedo, Alexander; Nicolaï, Johan; Annaert, Pieter; Naulaers, Gunnar; Allegaert, Karel
Abstract : Introduction: The optimal propofol dose and its safety for procedural sedation in neonates is controversial. The aim of this study was to perform a prospective propofol dose-finding study with pharmacodynamic (PD) assessment during (semi-)elective intubation in neonates. Methods: Patients were stratified in 4 groups by postmenstrual and postnatal age. The first patient in each group received 1 mg/kg intravenous propofol bolus. Dosing for the next patient was determined using the up-and-down method. Propofol ED50 doses [effective dose for successful intubation (as well as extubation in INSURE -intubation, surfactant, extubation-cases) in 50% of patients] were calculated, with simultaneous assessment of clinical scores, continuous vital sign monitoring and propofol blood concentrations (3 and 12h after dosing). Results: Thirty-five neonates (weight 540–3290 g) were included. Using initial and total propofol dose ranges of 0.5–2 and 0.5–4.5 mg/kg respectively, median propofol ED50 range for preterm neonates <10 days was 0.480–1.287 mg/kg. Clinical recovery was not attained at the end of the scoring period (21 minutes). A median decrease in mean arterial blood pressure (MABP) between −29.41% and −39.09% from baseline, and a short-lasting decrease in peripheral (SaO2 ) and regional cerebral (rScO2 ) oxygen saturation was documented. Variability in MABP, SaO2 and rScO2 was not explained by weight, age or propofol concentrations. Conclusions: Low propofol doses sufficiently sedate neonates for intubation, but clinical recovery takes time and is accompanied by permissive hypotension. Propofol ED50 doses are provided and need integration in a prospective validation approach. Finally, feasibility of continuous monitoring for neonatal pharmacodynamic research was demonstrated.